CRITERIES OF ELECTRICITY MARKET PARTICIPANTS IN THE CONDITIONS OF LIBERALIZATION OF POWER ENERGY SYSTEM ENTITIES - Bobonazarov, Bobomurod; Norboyev , Anvar; Boboqulov, Farrux (Innovatsion texnologiyalar, 2024)
This article widely covers the costs associated with the transfer of electrical energy to consumers, the role and importance of private electricity producers today, the stages of their development, trends associated with a decrease in the influence of state-owned energy companies in various relations in the energy system, an analysis of a number of shortcomings and problems of parallel growth stages development. Issues related to the effectiveness of the transition from a monopoly on the production and sale of electricity to a liberal market are also considered, materials are presented for researchers in the energy industry on the current successes of states that were among the first to form competitive market relations in the energy system. In addition to analyzing the requirements for optimizing the power system in current market conditions, the specifics of new models for the production and distribution of electricity, recommendations and proposals are also given aimed at mathematical solutions to the problems of controlling operating modes, taking into account the technical and economic factors of the electricity market. The mathematical forms of the criteria of a transport and distribution company for the distribution of electricity, the introduction into the system of criteria of a distribution company based on a single buyer model, a regional power supply company based on a wholesale consumer model and the inclusion of requirements in them, as well as benefits for the supplier and consumer of electrical energy are analyzed in detail.